2022
DOI: 10.1364/ao.457685
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent LIF/Mie ratio for sizing of micrometric ethanol droplets doped with Nile red

Abstract: The present study deals with droplet sizing based on laser-induced fluorescence (LIF) and Mie scattering for varied polarization of the utilized laser (parallel or perpendicular). The polarization-dependent LIF/Mie ratio is studied for micrometric droplets (25–60 µm) produced with a droplet generator. The investigations were carried out with the dye Nile red dissolved in ethanol and ethanol/iso-octane mixtures. A spectral absorption and fluorescence characterization at various dye and ethanol concentrations is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…A high-quality picture is obtained if the number of rays is not less than the number of array elements, i.e. 4N 2 .…”
Section: Ray Optics (Descartes') Canonical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-quality picture is obtained if the number of rays is not less than the number of array elements, i.e. 4N 2 .…”
Section: Ray Optics (Descartes') Canonical Calculationmentioning
confidence: 99%
“…A scientific area named the optics of microdroplets covers fundamental and applied problems such as droplet evaporation, laser-matter interactions, fluorescence, and spontaneous emission [1]. Among its latest advancements is the rapid determination of the size of spray droplets by optical response [2]. Recently, the certain regions have been noticed within an illuminated droplet where the inactivation of viruses by ultraviolet is difficult [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work conducted by (Koegl, et al, 2022) has shown that the polarization of the incident light in uences the proportionality between Mie signal and droplet diameter. Further investigation is undertaken here to study the in uence of the incident light polarization on the SLIPI-polarization technique.…”
Section: Effect Of the Incident Light Polarization On The Calibrationmentioning
confidence: 99%
“…Nile red can be dissolved in non-polar solvents like iso-octane, kerosene, Fragoltherm F12 and Marlotherm LH and can be utilized for the determination of the mixture composition of e.g. butanol/decane and ethanol/isooctane mixtures [32,33]. Nile red fluorescence shows a high temperature sensitivity when dissolved in kerosene and biofuel blends, while it is less temperature sensitive in fuels such as E20 (80 vol.% iso-octane, 20 vol.% ethanol) and E40 [16].…”
Section: Introductionmentioning
confidence: 99%